Program Kemitraan Masyarakat Kelompok Usaha Pembuatan Manisan Nangka dengan Pengering Rumah Kaca - Santosa, Budi ; Tantalu , Lorine ; Rozana (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2018)
Jackfruit sweets are one of the jackfruit processing with drying technology application to extend the shelf life, strengthen the aroma and taste, increase nutritional value, and increase the selling value of jackfruit. The problem with partners is the color of products that experience browning and do not have standard packaging. The method of carrying out the activities was carried out in a participatory manner through a series of programs, namely (1) technical guidance activities, (2) intensive business assistance with emphasis on improving product quality, formulating marketing strategies, and implementing business bookkeeping, and (3) facilitating product packaging design. The results of the activity showed that the community partnership program conducted in the sweets jackfruit business group was able to provide some improvements both in terms of candied jackfruit production and business management. The quality of the product produced is better in terms of appearance and packaging.